1975
DOI: 10.1021/bi00680a011
|View full text |Cite
|
Sign up to set email alerts
|

Conformations and structural transitions in polydeoxynucleotides

Abstract: Polydeoxynucleotides of different base sequence, the alternating poly[d(A-T)]-poly[d(A-T)], crab satellite DNA, on the one hand, and double-stranded homopolymer complexes poly[d(A)]-poly[d(T)], poly[d(I)]-poly[d(C)], on the other, display significant differences in their conformation and conformational transitions. Infrared linear dichroism investigations indicate that the alternating poly[d(A-T)]-poly[d(A-T)], enzymatically synthesized, adopts a lower humidity a well-expressed A* form in which stability is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
47
0
1

Year Published

1976
1976
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 34 publications
8
47
0
1
Order By: Relevance
“…Such strong base-base interactions give rise to intense CD spectra that are very sensitive to the overall solution conformation of these biomolecules. A number of reviews and books have appeared, during the last 30 years, specifically dealing with these topics [19][20][21][22]. Some clear correlations between a few characteristic CD spectral 4 features and the solution structure of various DNA molecules (B -DNA; A-DNA; C-DNA and so on) have been unambiguously established.…”
Section: Introductionmentioning
confidence: 99%
“…Such strong base-base interactions give rise to intense CD spectra that are very sensitive to the overall solution conformation of these biomolecules. A number of reviews and books have appeared, during the last 30 years, specifically dealing with these topics [19][20][21][22]. Some clear correlations between a few characteristic CD spectral 4 features and the solution structure of various DNA molecules (B -DNA; A-DNA; C-DNA and so on) have been unambiguously established.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown previously that differences in the conformation of the phosphate-ribose backbone, and particularly in the orientation of the phosphate groups and in conformational transitions, characterize synthetic DNAs composed of different base sequences (4). Thus, it has been found that the alternating polynucleotide poly [d(A-T)l undergoes a structural transition to the A form, whereas the double stranded homopolymer poly [d(A)].…”
Section: Introductionmentioning
confidence: 99%
“…poly [d(T)3 cannot adopt the A form (4)(5). It was thus proposed that the alteration of the backbone conformation as a consequence of different base sequences may have an important role in DNA recognition and protein interaction (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Information on conformational fluctuations in DNA is also of interest in connection with the use of spectroscopic tools (circular dichroism, infrared, Raman) to deduce the average conformational state of DNA (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%